A Community Awareness Project on Monkeypox (Mpox) and Enhanced Nursing Care for Patients: A Comprehensive Review - Priyanka Bansal (International Journal of Community Health Nursing And Practices, 2025)
Monkeypox (Mpox), a rare viral infection transmitted from animals to humans by the monkeypox virus, has attracted increasing attention due to its ability to spread between humans and its clinical similarities to other poxvirus diseases, including smallpox and chickenpox. Enhancing nursing care for monkeypox patients is imperative to manage and contain its spread effectively. On 15th October 2024, B.Sc. Nursing Interns of Holy Family College of Nursing, University of Delhi, conducted a community awareness project on ‘Mpox: Spreading awareness in the community setting’ at the Primary Health Centre (PHC), Palam, New Delhi. This was orchestrated under the community health nursing department of the college to spread awareness among the population attending clinics at the PHC. This initiative involved 21 dedicated B.Sc. Nursing Interns who came together to execute a collaborative project. This project focused on key strategies to improve nursing care for monkeypox patients, with an emphasis on differential diagnosis, preventive measures, and treatment options. On 14th August 2024, the Ministry of Health and Family Welfare (MOHFW) issued an advisory to the PHC, Palam administration, declaring monkeypox (Mpox) a Public Health Emergency of International Concern (PHEIC). As a result, preparedness and response efforts have been reviewed at the highest levels. Given the ongoing detection of new cases in various countries, the possibility of monkeypox occurring in India cannot be ruled out.
Keywords: Monkeypox (Mpox); chickenpox; nursing care; smallpox; viral infection